The status of global freshwater resources - Robert Luetkemeier; Ahmad Awad (Expertenkommission Forschung und Innovation (EFI), 2025)
Freshwater resources are vital for environmental health and human societies. Understanding their current status and future trends is critical for developing sustainable solutions. This study examines water quantity and quality on global and regional scales, with a specific focus on Germany. To assess water quantity, data from the Inter-Sectoral Impact Model Intercomparison Project (ISIMIP) was analyzed, providing insights into past, present, and future conditions. Water availability data and simulations of water withdrawals, incorporating socio-economic drivers, were used to estimate current and future water stress levels. For water quality, indicators from the Sustainable Development Goals Monitoring program and data from the Water Framework Directive were analyzed. The findings highlight uncertainties in assessing water stress and predicting future changes due to limited observational data and socio-economic variability. Models suggest declines in renewable water resources in arid and temperate regions, with possible increases in high-altitude and monsoon areas. While global water stress is expected to rise, reduced withdrawals in Germany may lead to lower stress levels. However, climate change-induced events like droughts and floods remain significant concerns. Water quality challenges show regional disparities. Globally, only 56% of water bodies meet good quality standards, with developed regions outperforming developing areas such as Sub-Saharan Africa and Central Asia in wastewater treatment. In Germany, despite advances in pollution control, water bodies face pressures from chemical pollutants, nutrient loads, and legacy contaminants like mercury. Only 9% of surface water bodies meet good ecological and chemical standards, and groundwater is compromised by nitrate and pesticide contamination, posing risks to drinking water and ecosystems. In conclusion, integrated and adaptive water management strategies are urgently needed to address the impacts of climate change, socio-economic developments, and pollution. Enhancing data quality and availability, especially in underrepresented regions, is essential for reliable projections and informed policy-making. Collaboration among stakeholders, governments, and technological innovations is critical for achieving sustainable water resource management for future generations.
Keywords: 330